Uwagi o podróży Juliana Ursyna Niemcewicza po Litwie w 1819 roku - Chachaj, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
In 1819, Julian Ursyn Niemcewicz took a journey around Lithuania. It was the sixth of his historical trips. The author summed up his observations of the state of Lithuania in following words: “How many dangerous, contagious diseases affect this part of the political body of our homeland!” The „plague” metaphor is developed further in the discussion. Niemcewicz describes “epidemics” that destroy society and the state, causing effects that are equally or more dangerous than material losses visible at first glance. He points to “plagues” resulting from political oppression and violence of invader on various levels of social life, as well as unwanted changes that dependent on the will of a man who succumbs to destructive influences.
Comments about Julian Ursyn Niemcewicz’s Journey around Lithuania in 1819
Keywords: Julian Ursyn Niemcewicz; travel; Lithuania; podróż; Litwa